THE MORAL DEVELOPMENT STAGES REPRESSENTED BY THE CHARACTERS IN WONDER NOVEL BY R.J. PALACIO - Widuri, Dwi Sinta Ayu; Valiantien, Nita Maya; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This study intended to examine the stages of moral development that occurred in R.J. Palacio’s Wonder novel as well as how the characters in Wonder novel develop their personality along with the moral development throughout the story. In conducting this research, the researcher used the descriptive qualitative method and moral development theory which was invented by Lawrence Kohlberg. In analyzing this study, the researcher used Wonder novel written by R.J. Palacio as the data source. Meanwhile, the data is presented in the form of words, clauses, phrases, sentences, and paragraphs related to the moral development theory as well as how the personality of the characters develop throughout the story. The results revealed that the way the characters developed their personality to the stages of moral development is based on the relationship between the characters’ comprehension of matters related to morals in line with how they respond to the matters. It was also found that the characters’ moral development relied on their understanding about moral itself and then following their conscience to make choices in their life.